Numerical simulation and deacidification of nanomagnetic enzyme conjugate in a liquid–solid magnetic fluidized bed. (March 2020) - Yue, Yingxue; Chen, Kuiren; Liu, Jingyang; Yu, Bohan; Jiang, Lianzhou; Yu, Dianyu; Wang, Liqi
Graphical abstract: Highlights: Free lipase TYPE II immobilized on magnetic Fe3O4/SiOx-g-P (GMA) nanoparticles. The movement of nano-magnetic particles in magnetic fluidized bed was simulated. Deacidification of rice bran oil in a multi-stage magnetic fluidized bed. The optimized conditions significantly improved enzymatic reaction. Abstract: The conventional deacidification method is difficult to achieve a better refining effect due to the high acid value in the rice bran crude oil, and the enzymatic esterification deacidification method can effectively reduce the acid value without generating chemical waste. In this study, the free lipase was immobilized on a magnetic polymer carrier Fe3 O4 /SiOx-g-P (GMA: glycidyl methacrylate) to obtain a immobilized lipase with a particle size of 105.30 ± 1.1 nm and an enzyme activity of 6580 ± 9.6 PLU/g (PLU: enzyme activity unit). Based on the batch deacidification process parameters, a multi-stage magnetic fluidized bed continuous circulation deacidification system was designed, and then the motion law of nanomagnetic immobilized lipase particles in liquid–solid magnetic fluidized bed was simulated by computer. When the iterative step was 5 × 10 −5 s, the open porosity of the porous plate was 35.0%, the rice bran oil flow rate was 3.0 mm/s, and the magnetic field strength was 25.0 mT, which was beneficial to the deacidification reaction of rice bran oil. Under the conditions of magnetic immobilized lipase dosage of 4.0%, the phytosterol dosage of 22.0%, the molecular sieve dosage of 10%, the esterification temperature of 78.0 °C and the FFA (free fatty acid) content in rice bran oil decreased to 1.5%, after 48 h of reaction. The conversion rate is 92.8%, which provides a theoretical basis for the subsequent guidance of magnetic fluidized bed enzymatic continuous deacidification.